FAKTOR-FAKTOR TERJADINYA TUNGGAKAN KENDARAAN RODA DUA DAN EMPAT PADA KANTOR SAMSAT KABUPATEN BULUKUMBA - Ainusy Syamsy; Harianto (Prodi Manajemen Universitas Syekh Yusuf Al Makassari Gowa, 2026)
This study aims to identify the factors causing motor vehicle tax arrears for two-wheeled and four-wheeled vehicles and to examine the efforts made by the Regional Revenue Unit (UPT Pendapatan Wilayah) of Bulukumba in addressing these arrears. The research was conducted at the Joint Samsat Office of Bulukumba Regency using a descriptive qualitative method. Data were collected through field observations, interviews with Samsat officers and taxpayers, and documentation of motor vehicle tax arrears reports for 2023–2024.The results indicate that motor vehicle tax arrears are influenced by several key factors, including low taxpayer awareness, unstable economic conditions or income, distance between taxpayers’ residences and payment locations, suboptimal service quality, and limited understanding of tax regulations. Economic factors and taxpayer awareness were found to be the dominant causes of delayed tax payments.Efforts undertaken by the Bulukumba Regional Revenue Unit to reduce tax arrears include increasing tax socialization, optimizing mobile Samsat services, improving service quality, conducting door-to-door data collection and billing, and collaborating with the police in enforcement operations. These measures are expected to enhance taxpayer compliance and reduce motor vehicle tax arrears, thereby contributing positively to the increase in Regional Original Revenue (PAD).